Conditions Facilitating the Computer Utilization in Teaching and Learning among Secondary School Teachers, Malaysia - Khalid, Fariza (2007)
Ely outlined (1999) eight conditions which will help increase the use of technological innovation in various education context: (a) “Dissatisfaction With Status Quo”, (b)” Knowledge And Skills Exist”, (c) “Resources Are Available”, (d) “Time Is Available”, (e) “Rewards And Incentives Exist For Participants”, (f) “Participation Is Expected And Encouraged”, (g) “Commitment By Those Involved” and (h) “Leadership Is Evident”. According to Ely, the presence of these conditions will facilitate the use of any technological innovation effectively. This research was conducted to identify the presence of Ely’s conditions in facilitating the use of computers in teaching and learning among teachers. Another purpose of this research was to determine the frequency of computer use in teaching and learning among secondary school teachers. The research also studied the relationship between frequency of computer use and the presence of Ely’s conditions. The sample for this research consisted of 429 teachers from four types of school, i.e. Day Schools, Fully Residential Schools, Religious Education Schools and Technical Education Schools. Data collection was carried out by using a set of questionnaire which included various items on computer use in teaching and learning, and teachers’ perception on the presence of Ely’s conditions. Data collected was analyzed using descriptive statistics, t-test, ANOVA and Pearson Correlation. The research finding indicated that all of the conditions were present in the school environment but the presence level was low. Only three out of eight conditions were perceived by respondents as present. The conditions were : (a) “Commitment By Those Who Involved”, (M = 18.59, S.D = 2.60), (b) “Leadership Is Evident”, (M = 18.48, S.D = 3.33) and (c) “Knowledge And Skills Exist”, (M = 17.78, S.P = 3.43). The finding also indicated that respondents were not sure about the presence of another five conditions: (a) “Rewards And Incentives Exist For Participants”, (M = 15.70, S.D = 1.84), (b) “Resources Are Available”, (M = 15.66, S.D = 3.52), (c) “Dissatisfaction Of Status Quo”, (M = 14.94, S.D = 3.14), (d) “Participation Is Expected And Encouraged”, (M = 14.69, S.D = 3.39) and (e) “Time Is Available”, (M = 13.62, S.P = 3.65). In terms of frequency, in average, teachers used computer as ‘tool’ 88 times per year, 8 times for computer as ‘tutor’ but less than once for computer as ‘tutee’. The result also indicated that there was a significant relationship between frequency of computer use in teaching and learning with most of Ely’s condition. As a conclusion, these research findings supported the role of Ely’s conditions in facilitating computer use in teaching and learning among secondary school teachers.